Perceptions of free enterprise and business: An examination of the status quo in South Africa - M. E. Nasser (South African Journal of Business Management, 1985)
Management has always contended that corporate employees have a very limited knowledge regarding the free enterprise and hence business system. The consequences of such a lack of understanding have always been apparent - worker dissatisfactions, labour unrest, conflict, and decreased productivity. This study is the first attempt to quantify the exact extent of this non-understanding among corporate employees in South Africa. This study has examined scientifically, via very extensive field work in 78 medium to large organizations situated in the PWV, western- and eastern Cape, and Natal regions, the perceptions of some 3 723 employees regarding business in South Africa. The analysis which covers six major categories of business comprehension, separated by education, position in the hierarchy, years of service, income level, sector, and race, provides very worrying evidence of the depth of the problem. The concomitant impacts accompanying the problem are also sketched so that management might better understand the nature and extent of the problems facing business in South Africa.
Keywords: 650